THE EFFECT OF BOREHOLE COLLAPSE ON THE STABILITY OF GROUP PILE FOUNDATIONS - Farahdiba, Farahdiba; Al Hanif, Basit; Setiawan, Andika; Nusyura Al Islami, Aulia (International Journal of Civil Engineering and Infrastructure, 2025)
The stability and load-bearing performance of pile group foundations are critical in infrastructure development, particularly in deep foundations such as bored piles. This study investigates the impact of borehole wall collapse on the load-bearing capacity and overall performance of a pile group foundation in North Jakarta, Indonesia. The borehole collapse occurred between depths of 25.2 m and 31.8 m, resulting in shortened pile lengths and reduced axial capacity. Subsurface investigations identified poorly graded sand (SP) within the collapsed zone, which contributed to borehole instability. Finite Element Method (FEM) analysis was performed to compare three scenarios: the original 48-meter design, the existing 22-meter condition post-collapse, and a redesigned pile group with additional piles. The 22meter design failed to meet the serviceability safety factor of 2.5, and several piles exceeded allowable limits. In contrast, the redesigned group fulfilled both bearing and displacement criteria, demonstrating improved structural performance. The findings emphasize the importance of design adaptation in response to construction anomalies to ensure the longterm safety and efficiency of deep foundations. keywords : Borehole Collapse, Pile Group Foundations, Bearing Capacity, FEM Analysis